revitalización cultural a través de la pintura expandida: una exploración a la identidad ecuatoriana. - Barzallo Barsallo, Jonathan Kevin (Machala: Universidad Tecnica de Machala, 2024)
The degree project entitled “Cultural Revitalization through Expanded Painting: An Exploration of Ecuadorian Identity” focuses on how expanded painting can act as a powerful medium for the recovery and valorization of Ecuadorian cultural identity. This artistic approach is notable for its ability to transcend the traditional boundaries of painting, incorporating diverse media and techniques that allow for a deeper and more meaningful exploration of culture and identity. The research begins with a conceptualization of the artistic object, exploring the evolution of painting from its beginnings to its contemporary state. Expanded painting is presented not only as an art form, but as a vehicle for critical reflection and cultural expression. This practice allows artists to question and challenge pre-established narratives, promoting a critical dialogue about contemporary culture and the power structures that shape it. In the Latin American context, expanded painting has gained relevance as a tool to address social and cultural issues. Artists in the region use this art form to challenge hegemonic narratives and explore issues such as inequality, marginalization and violence. Incorporating elements of Latin America's rich artistic and cultural tradition, expanded painting becomes a medium for resistance and vindication. In Ecuador, expanded painting represents not only an aesthetic evolution, but also an active response to the country's cultural and social dynamics. Ecuadorian artists employ this practice to interrogate power structures, stereotypical cultural representations and social injustices. By integrating diverse media and techniques, these artists seek to expand the reach of art beyond conventional spaces, bringing their work directly to the community. In this way, expanded painting acts as a catalyst for reflection and debate on issues relevant to Ecuadorian society. A case study in the city of Machala illustrates how expanded painting can give voice to marginalized and challenged experiences. Through installations, performances and community collaborations, artists in Machala use their art to question stereotypical and simplified representations of local culture. These artistic interventions invite the audience to reflect on issues ranging from identity and history to politics and the environment. Expanded painting, in this context, becomes a medium for social and cultural change, fostering a critical dialogue about the community's past, present and future. The degree project highlights the relevance of expanded painting as a tool for cultural revitalization and exploration of Ecuadorian identity. By challenging the traditional conventions of art, Ecuadorian artists seek to generate a profound impact on the collective consciousness, using their creativity to question power structures and promote a more inclusive and equitable society. Expanded painting thus stands as a powerful medium for the recovery of cultural identity and the promotion of critical reflection in contemporary society.
El proyecto de titulación titulado "Revitalización Cultural a través de la Pintura Expandida: Una Exploración de la Identidad Ecuatoriana" se centra en cómo la pintura expandida puede actuar como un medio poderoso para la recuperación y valorización de la identidad cultural ecuatoriana. Este enfoque artístico se destaca por su capacidad para trascender los límites tradicionales de la pintura, incorporando diversos medios y técnicas que permiten una exploración más profunda y significativa de la cultura y la identidad. La investigación comienza con una conceptualización del objeto artístico, explorando la evolución de la pintura desde sus inicios hasta su estado contemporáneo. La pintura expandida se presenta no solo como una forma de arte, sino como un vehículo para la reflexión crítica y la expresión cultural. Esta práctica permite a los artistas cuestionar y desafiar las narrativas preestablecidas, promoviendo un diálogo crítico sobre la cultura contemporánea y las estructuras de poder que la configuran. En el contexto latinoamericano, la pintura expandida ha ganado relevancia como una herramienta para abordar problemáticas sociales y culturales. Los artistas de la región utilizan esta forma de arte para desafiar las narrativas hegemónicas y explorar temas como la desigualdad, la marginalización y la violencia. Incorporando elementos de la rica tradición artística y cultural de América Latina, la pintura expandida se convierte en un medio para la resistencia y la reivindicación. En Ecuador, la pintura expandida no solo representa una evolución estética, sino también una respuesta activa a las dinámicas culturales y sociales del país. Los artistas ecuatorianos emplean esta práctica para interrogar las estructuras de poder, las representaciones culturales estereotipadas y las injusticias sociales. Mediante la integración de diversos medios y técnicas, estos artistas buscan ampliar el alcance del arte más allá de los espacios convencionales, llevando sus obras directamente a la comunidad. De este modo, la pintura expandida actúa como un catalizador para la reflexión y el debate sobre temas relevantes para la sociedad ecuatoriana. Un estudio de caso en la ciudad de Machala ilustra cómo la pintura expandida puede dar voz a experiencias marginadas y desafiadas. A través de instalaciones, performances y colaboraciones comunitarias, los artistas en Machala utilizan su arte para cuestionar las representaciones estereotipadas y simplificadas de la cultura local. Estas intervenciones artísticas invitan a la audiencia a reflexionar sobre temas que van desde la identidad y la historia hasta la política y el medio ambiente. La pintura expandida, en este contexto, se convierte en un medio para el cambio social y cultural, fomentando un diálogo crítico sobre el pasado, el presente y el futuro de la comunidad. El proyecto de titulación destaca la relevancia de la pintura expandida como una herramienta para la revitalización cultural y la exploración de la identidad ecuatoriana. Al desafiar las convenciones tradicionales del arte, los artistas ecuatorianos buscan generar un impacto profundo en la conciencia colectiva, utilizando su creatividad para cuestionar las estructuras de poder y promover una sociedad más inclusiva y equitativa. La pintura expandida se erige, así como un medio poderoso para la recuperación de la identidad cultural y la promoción de la reflexión crítica en la sociedad contemporánea.
Keywords: ARTE CONTEMPORANEO; PINTURA; RACISMO; AFROECUATORIANO